Simplified and integrated management system for responsible care (SIMS-RC) in chemical industries - N Khairlida, Muhamad; Lee, Khai Ern *; Mazlin, Mokhtar *; Goh, Choo Ta (Emerald, 2018)
Purpose–The purpose of this paper is to explore the barriers and challenges faced by chemical industries in Malaysia causing to the low participation in Responsible Care program. Also, this paper aims to propose a solution to address the issues in implementing Responsible Care by introducing a Simplified and Integrated Management System for Responsible Care. Design/methodology/approach – A questionnaire was distributed to 132 Responsible Care signatory companies in Malaysia, and they were given a week to return it via e-mail. Combining the inputs from the survey and document analysis, a Simplified and Integrated Management System for Responsible Care (SIMS-RC) was proposed. Findings – Responsible Care signatory companies faced barriers in implementing product stewardship code and they also faced challenges in getting employees’ commitment from all levels. Taking the inputs received from Responsible Care signatory companies and document analysis,an SIMS-RC was proposed as a closed-loop process which consists of quality, environmental, health and safety management system. Research limitations/implications– Some of the chemical companies were unable to share their thoughts in the survey due to the companies’ confidential reason. Originality/value – Abundant literature has discussed about the limitation of Responsible Care that needs to be improved.Therefore,several elements and procedures of the program need to be revised and innovated to help the signatory companies to continuously improve their performances and encourage more participation in Responsible Care program.The findings will add value to the current body of knowledge and Responsible Care signatory companies which seek to improve Responsible Care implementation through an integrated management system approach. The proposed SIMS-RC is a simple, integrated, holistic and process-oriented management system in which it blends Responsible Care in to quality,environmental,health and safety management system.